An Efficient Method to Generate Chromosomal Rearrangements by Targeted DNA Double-Strand Breaks in Drosophila melanogaster - Egli, Dieter; Hafen, Ernst; Schaffner, Walter (Genome Research, 2004)
Homologous recombination (HR) is an indispensable tool to modify the genome of yeast and mammals. More recently HR is also being used for gene targeting in Drosophila. Here we show that HR can be used efficiently to engineer chromosomal rearrangements such as pericentric and paracentric inversions and translocations in Drosophila. Two chromosomal double-strand breaks (DSBs), introduced by the rare-cutting I-SceI endonuclease on two different mobile elements sharing homologous sequences, are sufficient to promote rearrangements at a frequency of 1% to 4%. Such rearrangements, once generated by HR, can be reverted by Cre recombinase. However, Cre-mediated recombination efficiency drops with increasing distance between recombination sites, unlike HR. We therefore speculate that physical constraints on chromosomal movement are modulated during DSB repair, to facilitate the homology search throughout the genome.